(untitled) (Colombia Medica, 2019)
The possibilities of editorial advancement of a journal are defined by the understanding and adoption of technological resources, the organization of processes and the permanent updating of the editorial committee. The most important factor seems to be an editorial committee that interprets the needs of authors, readers and all participants in editorial processes, and accordingly demands technical needs to improve communication and dissemination of scientific content. More than 20 years ago, the editors of Colombia Médica understood the potential of the incipient internet, opted for an electronic journal and, with calculation, risked abandoning paper printing with good results. In the last decade, with the same vision and knowledge of the limitations of managing a magazine as a web page, the editorial content manager Open Journal System (OJS) was implemented, which from the beginning was understood as a system for managing the editorial process and of the publication. With the acceptance of the journal in the Pubmed / Medline bibliographic database, the editorial body faced the need to publish in the XML-JATS (eXtensible Markup Language-Journal Article Tag Suite) language, little known among Latin American publishers. The support of the SciELO Brazil project (Scientific Electronic Library Online) to understand and implement this language in the articles was valuable. This was the technical requirement that the PubMed Central full-text database demanded to accept the journal in its open access collection 1. The reward was almost immediate: the reading public and the scientists who required the journal articles expanded to the 5 continents.